Contingent negative variation and its relation to time estimation: a theoretical evaluation - Van Rijn, Hedderik; Kononowicz, Tadeusz W.; Meck, Warren H.; Ng, Kwun Kei; Penney, Trevor B. (Frontiers in Integrative Neuroscience, 2011)
The relation between the contingent negative variation (CNV) and time estimation is evaluated in terms of temporal accumulation and preparation processes. The conclusion is that the CNV as measured at fronto-central and parietal-central areas is not a direct reflection of the underlying interval timing mechanism(s), but more likely represents a time-based response preparation/decision-making process.